Barriers to research in palliative care: A systematic literature review. (April 2015) - Blum, David; Inauen, Roman; Binswanger, Jacqueline; Strasser, Florian
Abstract : Introduction: Research in palliative care (PC) is often regarded as challenging due to the vulnerability of the population and other peculiarities. We aim to systematically identify barriers to research in PC in the literature. Methods: The electronic databases CINAHL, MEDLINE were searched for papers published in the last 25 years. Citations and then abstracts were screened for inclusion. Original papers were included on first-level analysis. On a second level reviews, reports, and position papers were analyzed. Papers containing a direct patient report were specifically analyzed. Barriers were categorized (ethical considerations, financial and time expenses, study design and methodology, human resources and politics) and results quantified. Results: Twenty-one original papers and 65 other papers were included. Five studies involved patients directly, five were systematic reviews, three were study experiences, and seven were surveys or workshop reports. Most papers originated from UK, USA, or Norwegian Universities. Ethics and methods were the most often mentioned categories on both levels. Accrual, attrition, and gatekeeping were frequently named barriers. Complex invasive studies or possible side effects hinder patients' participation, as patients are often willing to participate for altruistic motivations. Discussion: Barriers to PC research are ethical concerns and methodological challenges. Possible strategies to overcome methodological barriers include international collaborative efforts to include more patients and improve study designs. Ethical barriers indicate the need for patient involvement in the research development process and tailoring research specifically to the PC population.